Modified Aggregates for Mitigating Anodic Acidification in Impressed Current Cathodic Protection Systems Toward Infrastructure Modernization - Yuxin Xing; Zhangmin Zhang; Qiang You; Jie Hu (Buildings)
In the context of infrastructure modernization, enhancing the durability of reinforced concrete (RC) structures is crucial for achieving sustainable and resilient development. Impressed current cathodic protection (ICCP) is a popular technique to improve corrosion resistance of RC structures exposed to chloride-rich environments but may also induce localized acidification in the external anode mortar due to continuous OH− consumption and H+ generation. This phenomenon leads to the dissolution of calcium hydroxide and acidification erosion damage on the anode metal and mortar, undermining the long-term performance of the protection system. This study uses modified aggregates that are incorporated with Ca(OH)2 to improve the corrosion resistance of anode metal and mortar. Results from electrochemical measurements, pH monitoring, and XRD analysis show that the Ca(OH)2-loaded aggregates extended the stable alkaline buffer time of simulated pore solution during ICCP by 1.5 to 2 times longer and exhibited good resistance to the mortar acidification. These findings offer a promising pathway for safeguarding RC structures and advancing infrastructure modernization by integrating protective functionalities at the material level.